Enhancing Hospital Service Quality and Patient Safety through the MIRACLE Model: A Partial Least Squares Equation Approach - Marpaung, Yahya; Dorisnita,; Hartati,; Usniza, Mila; Matari, Mindi Claudia (International Journal of Statistics in Medical Research, 2023)
Objective: Give a background why this model is worthwhile by briefly highlighting the current health system and how this study may help to improve this system. This study aims to assess the impact of the MIRACLE model onquality enhancement and patient safety within healthcare settings. Study Design: Employing a cross-sectional design, this research centers on four key variables and 19 corresponding indicators. Data were collected using a questionnaire distributed via Google Forms, targeting heads of work units at M. Djamil Central General Hospital in Padang, Indonesia. Method: The analysis utilizes the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique to evaluate variable relationships. The variables studied are Communitarian, Apprenticing Affinity, Managing, and Quality and Patient Safety, with indicators integrated into the questionnaire. Results: Communitarian and Apprenticing Affinity emerged as influential factors directly impacting quality of health servicesand patient safety, moderated by Managing variable. Research findings reveal a significant positive impact of the Apprenticing Affinity variable on Managing (p-value = 0.013), underlining its significance in hospital management. Moreover, Apprenticing Affinity significantly affects quality and patient safety (p-value = 0.00), highlighting its pivotal role in healthcare enhancement. Similarly, the Communitarian variable significantly influences Managing (p-value = 0.11), notably impacting quality and patient safety (p-value = 0.00). However, Managing alone does not significantly impact quality and patient safety (p-value = 0.15). Indirectly, the research unveils that the Managing-moderated Apprenticing Affinity variable lacks significant influence on quality and patient safety (p-value = 0.268). Similarly, Managing-moderated Communitarian influence does not substantially impact quality and patient safety (p-value = 0.411). Conclusion: This study highlights the substantial impact of Communitarian and Apprenticing Affinity, moderated by Managing, on quality and patient safety. Notably, Managing alone lacks direct influence. These findings underscore the significance of cultivating collaborative, learning-oriented environments, alongside effective management practices, to bolster healthcare quality and patient safety.